New Praestochrysis and Notes on Described Species From the Oriental Region (Hymenoptera, Chrysididae) - R. M. Bohart (Psyche: A Journal of Entomology)
The genus Praestochrysis Linsenmaier is distinguished by having 5 distinct teeth on tergum III and a rather stout antenna. In any case the latter has flagellomere I less than 3 times as long as broad. Bohart (1986, Insecta Mundi 1:148-154) gave a key to species of the Ethiopian Region. One additional species, lamborni, is here described from that region. It keys out to couplet 6 in the 1986 paper but differs in having no transverse frontal carina.